Molecular Sequencing and Immunological Analysis of Trichomonas vaginalis in Women in Wasit province, Iraq - Hraija, Baraa Abdulsalam (American Journal of Biology and Natural Sciences, 2025)
Trichomonas vaginalis is the most common parasitic sexually transmitted infection, which can lead to more severe reproductive health complications. Despite, T. vaginalis infection remains fairly diagnosed due to asymptomatic presentation or non-specific symptoms, necessitating robust diagnostic methodologies for accurate identification and treatment. Identifying the prevalence rate of human trichomoniasis in women of Wasit province (Iraq) using the rapid test and molecular PCR with sequencing and phylogenetic analysis of T. vaginalis isolates. Association of immunity to T. vaginalis infection through measurement the levels of cysteinyl leukotrienes (CysLTs), interleukin 8 (IL-8), and leukotriene B4 (LTB4) was aimed. Totally, 291 women having various socio-demographic factors and reproductive disorders were admitted to the private gynecological clinics in Wasit province (Iraq) during March-June (2025) and selected to the present study. All study women were subjected to sampling of vaginal swabs that processed and tested directly by the rapid test and then by molecular assay. Additionally, venous blood was drained, centrifuged, and the sera were utilized for measurement of immune markers. The findings of rapid test in vaginal swabs recorded that 3.78% of study women were having a positive reactivity to T. vaginalis antigen. Molecularly, 5.84% of study women were positively infected by T. vaginalis using the conventional PCR. Phylogenetic analysis of study T. vaginalis isolates identified a marked identity with the NCBI-BLAST T. vaginalis Indian T. vaginalis isolate (ID: JF513197.1). In comparison with the negatively individuals, the positively T. vaginalis infected women were reported a significant elevation in values of CysLTs (275.09 ± 17.09 pg/ml), IL-8 (130.83 ± 6.04 pg/ml), and LTB4 (1512.059 ± 90.73 pg/ml). This study indicates that rapid test and/or molecular PCR can provide important data about the prevalence of T. vaginals in Iraqi population of various socio-demographic aspects who appeared with or without clinical symptoms. Phylogenetically, this study showed that the local T. vaginalis isolates were markedly identical to the Indian T. vaginalis isolates; however, moreover sequencing and genetic information are greatly necessary as such data can be utilized in epidemiology of parasitic infection. Serological elevation of immune markers in positively infected women might further complicates the pathological landscape and enhance the inflammatory cascade with promoting the proliferation of pathogenic bacteria.